2009
DOI: 10.1194/jlr.r800062-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

5-Lipoxygenase: mechanisms of regulation

Abstract: 5-Lipoxygenase (5-LO) catalyzes two steps in biosynthesis of leukotrienes (LTs), a group of lipid mediators of inflammation derived from arachidonic acid (AA). LT antagonists are used in treatment of asthma; more recently a potential role also in atherosclerosis has raised considerable interest. Furthermore, possible effects of 5-LO metabolites in relation to tumorigenesis have emerged. Thus, an understanding of the biochemistry of this lipoxygenase has potential implications for treatment of various diseases.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
115
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(129 citation statements)
references
References 53 publications
5
115
0
2
Order By: Relevance
“…Our results showed that EGR-1 siRNA was effective in reducing PlGF-mediated 5-LO and FLAP mRNA expression. The role of Egr-1 in 5-LO transcription is consistent with the presence of several GC-boxes in the human 5-LO gene promoter that are proximal to the transcription start site and are recognized by transcription factors Sp1 and Egr-1 (34,38). However, PlGF-induced FLAP mRNA expression was attenuated by both EGR-1 siRNA and HIF-1␣ siRNA, indicating direct or indirect roles of these transcription factors.…”
Section: Discussionsupporting
confidence: 66%
“…Our results showed that EGR-1 siRNA was effective in reducing PlGF-mediated 5-LO and FLAP mRNA expression. The role of Egr-1 in 5-LO transcription is consistent with the presence of several GC-boxes in the human 5-LO gene promoter that are proximal to the transcription start site and are recognized by transcription factors Sp1 and Egr-1 (34,38). However, PlGF-induced FLAP mRNA expression was attenuated by both EGR-1 siRNA and HIF-1␣ siRNA, indicating direct or indirect roles of these transcription factors.…”
Section: Discussionsupporting
confidence: 66%
“…As shown in Fig. S1, positions Y42 and Y53 seem to be very close to the membrane interacting tryptophanes (W13, W75, W102) and the calcium binding loop of 5-LO (N43, D44, E46), which are both important for activation mediated translocation of 5-LO to the membrane [3]. Furthermore, Y445 interacts with the loop in which R518 is located, which is part of a nuclear import sequence and near the phosphorylation site S523 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…S3). 5-LO is upregulated in MM6 cells after cell differentiation (TGF-b and 1a,25-dihydroxyvitamin D 3 ) and, since it was seen phosphorylated at Ser271 without further treatment, it seems that the phosphorylation event is not connected to a specific stimulus for 5-LO activity but is rather constitutive. However, the signal intensity for the phosphopeptide in the mass spectra was low and the enrichment procedure was not successful for many of the examined samples.…”
Section: Maldi-ms Analysis Of Immunoprecipitated Samples From Mm6 Cellsmentioning
confidence: 99%
See 2 more Smart Citations